Chinese ink coated melamine foam with Joule heating and photothermal effect for strain sensor and seawater desalination. (October 2021) - Cao, Xiang; Liu, Hongzhong; Cai, Jiabing; Chen, Linhong; Yang, Xiya; Liu, Mingxian
Highlights: A multifunctional Chinese ink coated melamine foam was fabricated. The strain sensing, Joule heating and photothermal performance are studied. Conductive foams are able to sensitively detect human physiological activities. Superior photothermal property endows the composite good desalination ability. Abstract: Chinese ink is a common painting material with intrinsic color of black, excellent water-dispersion stability, and proper fluidity. Herein, a conductive melamine foam (CMF) composite with various features was fabricated through a dip-coating method to assemble Chinese ink carbon nanoparticles (ICN) on the foam. The CMF combines the advantages of strain sensing, Joule heating and photothermal performance. The resistance of CMF changes rapidly upon compression or tension, so CMF is employed to monitor physiological activities. Moreover, CMF exhibits excellent Joule heating property, which is applied to sensitively detect the fingers bending action. In addition, CMF shows good photothermal performance under near-infrared light (NIR) and simulated sunlight, which is capable to carry out desalination with high evaporation rate and efficiency. This study provides a new strategy to construct a multifunctional light-absorbing and conductive device with very cheap raw materials, which shows great potentials in smart sensor and desalination.